PENGEMBANGAN MODUL BERBASIS GENDER DAN KEBHINEKAAN DI KELAS III SD SUBTEMA PERKEMBANGAN TEKNOLOGI PRODUKSI PANGAN - Siti Aisyah; Zaka Hadikusuma Ramadan (Universitas Negeri Medan, 2022)
Abstract: This study aims to develop teaching materials based on gender and diversity modules in class III on the sub-theme of the development of food production technology and determine the feasibility of teaching materials modules that have been developed for students at SDN 193 Pekanbaru. This research method uses Research and Development (R & D) which begins with the analysis stage followed by the design, development and product assessment stages. While the subjects in this study were 1 teacher, 2 students and 2 design experts, 2 linguists, and 2 thematic material experts. The results of the study show that the gender and diversity-based modules that have been developed have met the validity aspect. Gender and diversity-based modules in class III on the sub-theme of food production technology development are suitable for use based on the assessment of experts, namely material experts with 94% with very valid criteria, 89% design experts with very valid criteria, and linguists 87% with very valid criteria. . The average percentage of validation results is 90% with a valid category without revision. Based on this, the module based on gender and diversity in class III on the sub-theme of the development of food production technology is considered very valid to be implemented. Keywords: Gender, Diversity, Module, Development Abstrak: Penelitian ini bertujuan untuk mengembangkan bahan ajar modul berbasis gender dan kebhinekaan di kelas III pada subtema perkembangan teknologi produksi pangan dan mengetahui kelayakan bahan ajar modul yang telah dikembangkan untuk peserta didik di SDN 193 Pekanbaru. Metode penelitian ini menggunakan Research and Development (R & D) yang diawali dengan tahap analisis dilanjutkan tahap perancangan, pengembangan dan penilaian produk. Sedangkan subjek dalam penelitian ini adalah 1 guru, 2 siswa serta 2 ahli desain, 2 ahli bahasa, dan 2 ahli materi tematik. Hasil penelitian menunjukkan modul berbasis gender dan kebhinekaan yang dikembangkan telah memenuhi aspek validitas. Modul berbasis gender dan kebhinekaan di kelas III pada subtema perkembangan teknologi produksi pangan layak digunakan berdasarkan penilaian dari para ahli yaitu ahli materi dengan 94% dengan kriteria sangat valid, ahli desain 89% dengan kriteria sangat valid, dan ahli bahasa 87% dengan kriteria sangat valid. Adapun presentase rata-rata hasil validasi 90% dengan kategori valid tanpa revisi. Berdasarkan hal tersebut modul berbasis gender dan kebhinekaan di kelas III pada subtema perkembangan teknologi produksi pangan dinilai sangat valid untuk diimplementasikan. Kata kunci : Gender, Kebhinekaan, Modul, Pengembangan